2013
DOI: 10.1007/s10464-013-9614-2
|View full text |Cite
|
Sign up to set email alerts
|

A Life Domains Perspective on Acculturation and Psychological Adjustment: A Study of Refugees from the Former Soviet Union

Abstract: The study articulates a contextual approach to research on acculturation of immigrants, suggesting that the relationship between acculturation and adjustment is dependent on the cultural demands of the life domains considered. Specifically, the study investigated the mediating effects of adjustment in occupational and social life domains on the relationship between acculturation and psychological adjustment for 391 refugees from the former Soviet Union. The study used bilinear measures of acculturation to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 55 publications
0
78
0
Order By: Relevance
“…Among former Soviet Union refugees in the United States, coethnic social support was associated with better mental health (Birman et al. ). Hispanics may find support and familiarity in barrio communities (Pérez‐Escamilla and Putnik ; Riosmena, Wong, and Palloni ), where health benefits have been observed for first‐generation (Cagney, Browning, and Wallace ) and second‐generation Hispanics (Lee and Ferraro ).…”
Section: Neighborhood Ethnocultural Compositionmentioning
confidence: 99%
“…Among former Soviet Union refugees in the United States, coethnic social support was associated with better mental health (Birman et al. ). Hispanics may find support and familiarity in barrio communities (Pérez‐Escamilla and Putnik ; Riosmena, Wong, and Palloni ), where health benefits have been observed for first‐generation (Cagney, Browning, and Wallace ) and second‐generation Hispanics (Lee and Ferraro ).…”
Section: Neighborhood Ethnocultural Compositionmentioning
confidence: 99%
“…Greater acculturation to US culture among refugee young adults was related to depression only when parents' acculturation to US culture was low; this was not the case when parents' acculturation to US culture was high [26]. A study by Birman and colleagues found that acculturation both to the native culture and to the host culture were related to mental health of Former Soviet refugees but in different ways [27]. Acculturation to American culture was positively related to life satisfaction because of its effects on occupational success, while acculturation to their native Russian culture was related to life satisfaction because of social support from their co-ethnic social network [27].…”
Section: Introductionmentioning
confidence: 99%
“…Christian, Gadfield, Giles, & Taylor, 1976;Okamura, 1981), interest in the dynamic nature of ethnic identity has recently increased, as scholars attempt to identify the situational contexts in which certain identities become more or less important and understand the implications of identity dynamics for cross-cultural adaptation (e.g. Birman, Simon, Chan, & Tran, 2014;Doucerain, Dere, & Ryder, 2013). For instance, sociocognitive perspectives on culture demonstrate that bicultural persons tend to switch cognitive frames in response to cultural primes (Hong, Morris, Chiu & Benet-Martínez, 2000).…”
mentioning
confidence: 99%